Glutamate Supplementation Improves Growth Performance, Rumen Fermentation, and Serum Metabolites in Heat-Stressed Hu Sheep - Li, Chuan; Zhang, Jiantong; Li, Yanjiao; Zhao, Xianghui; Liang, Huan; Li, Kairong; Qu, Mingren; Qiu, Qinghua; Ouyang, Kehui (Frontiers in Nutrition, 2022)
This study evaluated the effect of glutamate supplementation on the physiological parameters of heat-stressed Hu sheep. Forty-eight male Hu sheep with an average initial body weight of 17.74 ± 0.17 kg were randomly divided into two groups: The control group (CON) was fed a basal diet and a treatment group (GLU) was fed a basal diet + 3 g/head/day of L-glutamate. There were six replications in each group with four sheep in each replication for a 90 d feeding test. Growth performance, serum biochemistry, and serum hormones were measured during phase 1 (1–30 d), phase 2 (31–60 d), and phase 3 (61–90 d) of the experiment; rumen fermentation characteristics, nutrient digestibility, and slaughter performance were measured at the end of the experimental periods. There were no differences in growth performance, serum biochemical indices, and immune indices between CON and GLU during phases 1 and 2. However, a higher average daily gain, a lower average daily feed intake, and a lower F:G ratio (ADFI/ADG) were observed in GLU during phase 3 (P < 0.05). Serum levels of glutamate, globulin, immunoglobulin A, immunoglobulin G, immunoglobulin M, and growth hormone in GLU were higher than those in CON only on day 90 (P < 0.05). Serum levels of heat shock protein 70, adrenocorticotrophic hormone, corticosterone, triiodothyronine, and tetraiodothyronine in GLU were lower than those in CON on day 90 (P < 0.05). At the end of the experiment, ruminal pH, microbial crude protein, ammonia nitrogen, and isovalerate concentrations in GLU were higher than those in CON (P < 0.05). The apparent digestibility of dry matter, organic matter, and crude protein in GLU was higher than in CON (P < 0.05). There were no differences in carcass traits and organ indices but spleen weight and spleen index tended to be higher in GLU. In conclusion, dietary glutamate supplementation improved rumen fermentation, increased nutrition digestibility and metabolism, enhanced immunity, and promoted growth performance of heat-stressed Hu sheep. This suggests that a longer period of glutamate supplementation (not less than 60 d) at a level of 3 g/head/day is beneficial to Hu sheep under heat stress.